PARENTING AND DIGITAL LITERACY ASSISTANCE FOR YOUNG MOTHERS IN EARLY CHILDHOOD EDUCATION IN PREVENTING THE RISK OF INTERNET MEDIA THROUGH THE CONTROLLING GEDGET APPLICATION - Asmahasanah, Salati; Triwoelandari, Retno; Al Ikhsan, Safaruddin Hidayat; Ritzkal, Ritzkal (LPPM Univ. Ibn Khaldun Bogor, 2025)
This community service activity was motivated by the increasing gadget addiction among early childhood children in Indonesia, with 88.99% using the internet—mainly for social media (66.13%) and entertainment (63.08%). This critical period, known as the golden age of development, requires strong parental guidance, yet many parents lack awareness of how to manage their children’s cellphone use effectively. The program, titled Parenting Assistance and Digital Literacy for Young Mothers in Preventing the Risk of Internet Media through Controlling Violence in Children, aimed to enhance young mothers’ competence in supervising and controlling their children’s internet use to mitigate its negative effects. Conducted at the Nurul Albarokah Foundation, PAUD Albarokah, Parung, Bogor Regency, this activity had several objectives: (1) to provide parenting guidance through seminars and training, (2) to improve digital literacy among young mothers, (3) to train them in using the Google Family Link feature for gadget control, (4) to prevent internet addiction and its adverse effects on children’s growth, intelligence, and morals, and (5) to develop intelligent and resilient mothers. The increasing exposure of children to the internet highlights the urgent need for parental supervision to prevent potential harms such as cyberbullying, violent behavior, and access to inappropriate content.